Congenital biliary anomaly with secondary cholangiohepatitis in a Siamese cross kitten - Yiew, Xiu Ting; Watanabe, Malaika; Leong, Zi Ping; Rahman, N.; Mohamed Mustapha, Noordin; Khor, Kuan Hua (Veterinary Association Malaysia, 2016)
A 5-month-old Siamese cross kitten was presented with jaundice and a palpable abdominal mass at the right cranial quadrant. The extra-hepatic biliary system was markedly distended upon abdominal ultrasonography. Complete bile duct obstruction was ruled out due to the presence of urobilinogen, light brown stool, and consistently normal alkaline phosphatase (ALP) levels. Head tremors developed on the second day of hospitalization. Tentative diagnoses of congenital biliary anomaly and hepatic encephalopathy were derived and exploratory laparotomy revealed a severely distended and tortuous bile duct indistinguishable from the gallbladder with negative duodenal filling. Modified cholechoduodenostomy was performed however the kitten did not recover from general anaesthesia. Secondary cholangiohepatitis and hepatic encephalopathy were confirmed upon histopathologic examination.Primary congenital biliary atresia or choledochal cyst with secondary cholangiohepatitis was suspected. Biliary anomalies are rare in cats with only two cases reported in the literature. These conditions are often challenging to diagnose and due to the limited treatment options, have a poor prognosis.